2003
DOI: 10.1002/neu.10228
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and hormone influences on tyrosine hydroxylase immunoreactive cells in the leopard frog

Abstract: We examined sex differences in tyrosine hydroxylase immunoreactive (TH-ir) cell populations in the preoptic area (POA), suprachiasmatic nucleus (SCN), posterior tuberculum (TP), and caudal hypothalamus (Hy) in the leopard frog (Rana pipiens), in addition to the effects of natural variation in sex steroid hormones on these same populations in both sexes. All four of these populations have been shown to be dopaminergic. Gonadal sex, androgens, and estrogen all influenced TH-ir cell numbers, but in a complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 62 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…Although our assays are unable to discern whether the androgen pattern is due to a change in testosterone, dihydrotestosterone or both, previous studies have reported that reproductively active female anurans exhibit significantly higher circulating levels of testosterone than dihydrotestosterone (Harvey et al, 1997;Wilczynski et al, 2003;Medina et al, 2004). In addition, levels of testosterone in some female anurans are comparable to male levels and are generally higher than the concentration of estrogen in the plasma (d 'Istria et al, 1974;Licht et al, 1983;Harvey et al, 1997;Wilczynski et al, 2003;Medina et al, 2004).…”
Section: Discussionmentioning
confidence: 63%
“…Although our assays are unable to discern whether the androgen pattern is due to a change in testosterone, dihydrotestosterone or both, previous studies have reported that reproductively active female anurans exhibit significantly higher circulating levels of testosterone than dihydrotestosterone (Harvey et al, 1997;Wilczynski et al, 2003;Medina et al, 2004). In addition, levels of testosterone in some female anurans are comparable to male levels and are generally higher than the concentration of estrogen in the plasma (d 'Istria et al, 1974;Licht et al, 1983;Harvey et al, 1997;Wilczynski et al, 2003;Medina et al, 2004).…”
Section: Discussionmentioning
confidence: 63%
“…Circulating plasma testosterone levels are as high in reproductive females as in males (although in males dihydrotestosterone is higher) and higher than estrogen levels in many anuran species (d 'Istria et al, 1974;Licht et al, 1983;Iela et al, 1986;Itoh and Ishii, 1990;Harvey et al, 1997;Wilczynski et al, 2003;Medina et al, 2004;. The behavioral relevance of this, if any, is unclear.…”
Section: Steroid Hormones and Courtship Behavior In Female Amphibiansmentioning
confidence: 99%
“…We describe here the dopaminergic system in P. pustulosus compared with the brains of other anurans, including the African clawed frog ( X. laevis [González et al, 1993]), the marsh frog ( R. ridibunda [González and Smeets, 1991]), the fire-bellied toad ( B. orientalis [Endepols et al, 2006]), and the northern leopard frog ( R. pipiens [Wilczynski et al, 2003]). Overall the distribution of dopaminergic neurons and fibers is highly conserved across amphibians [González and Smeets, 1994] ( table 1 ).…”
Section: Comparison Of the Dopamine System With Other Amphibiansmentioning
confidence: 99%
“…The distribution of dopamine-producing cells in the amphibian brain in particular has been well studied in several species including the African clawed frog ( Xenopus laevis [González et al, 1993]), the marsh frog ( Rana ridibunda [González and Smeets, 1991]), the fire-bellied toad ( Bombina orientalis [Endepols et al, 2006]), and the northern leopard frog ( Rana pipiens [Wilczynski et al, 2003]). However, it has recently become apparent that all vertebrates except mammals have 2 paralogs encoding TH: th1 and th2 [Filippi et al, 2010;Yamamoto et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation